Lady Macbeth : [large type] a novel - Reid, Ava (Thorndike Press, a part of Gale, a Cengage Company, 2024)
Marrying a Scottish warrior, Lady Macbeth must use all her wiles and hidden witchcraft to survive his hostile, suspicious court but unbeknownst to her, he has occult secrets of his own and a prophecy that girds him like armor, making her magic even more dangerous as it threatens the order of the world.